Effectiveness of Faradism Under Pressure Versus Complex Decongestive Therapy in Subjects with Peripheral Oedema - Chelcy S Jaju1 , Mandar Malawade2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Oedema is defined as excessive accumulation of free fluid in interstitial tissue spaces andserous cavities. The oedema may be of 2 main types: Localized when a particular organ or limb is involvede.g. lymphatic oedema, inflammatory oedema, allergic oedema and generalized when it is systemic indistribution, particularly seen in the subcutaneous tissues. The gold standard therapy for lymphedema iscomplex decongestive therapy (CDT). The first stage of CDT includes manual lymphatic drainage (MLD),compression therapy, exercise, and good skin care. The second phase, consisting of self-managing lymphaticmassage, daily use of compression garments, and self-directed continuation of the exercises, should beimplemented only after the completion of the first phase. Also, Faradism under pressure (FUP) is beneficialin oedematous conditions. In FUP, the pumping action of the alternate muscle contraction and relaxation,brings about increased venous and lymphatic return. The fluid is propelled towards the heart by an inwardpressure on the tissue spaces and veins caused by the contraction of the muscle.Objectives: The objectives of the study were as follows: To determine effect of faradism under pressure inperipheral oedema. To determine effect of complex decongestive therapy. To compare the effect of faradismunder pressure and complex decongestive therapy in peripheral oedematous conditions.Methods: Ethical clearance was obtained from the institutional ethical committee. A total of 20 subjectswere assessed and all were included in the study based on inclusion criteria. Oedema was diagnosed usingvolumetric and girth assessment. Results: Intra-group statistical analysis of intervention group, pre-postvolumetric measurement score was 33.6 ±9.192 and was found to be extremely significant and pre-post girthassessment score was 2.540 ± 0.9513 which was extremely significant. Conclusion: We found that both FUPand CDT were significantly effective in reducing peripheral oedema but CDT was more effective comparedto FUP. This treatment was effective by reducing the volumetric and girth measurements which improvedquality of life of patients.